Binder, binder composition, preparation method, negative electrode slurry, negative electrode sheet, secondary battery, battery module, battery pack, and electric device

A core-shell structured binder with specific temperature ranges and composition addresses the balance between negative electrode sheet processing and battery cell performance, reducing impedance and improving adhesion to enhance battery cell dynamics.

JP2025502184AActive Publication Date: 2025-01-24CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024541725
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-07-07
Publication Date
2025-01-24
Estimated Expiration
2042-07-07

AI Technical Summary

Technical Problem

Existing binders used in negative electrode sheets for secondary batteries, such as styrene-butadiene rubber and carboxymethyl cellulose sodium, fail to balance the processing performance of the sheet with the performance of the battery cells, leading to issues like sedimentation, decreased viscosity, reduced particle adhesion, and impaired dynamic performance.

Method used

A core-shell structured binder is developed, where the core material has a glass transition temperature ranging from -50 °C to 0 °C and the shell material from 60 °C to 100 °C, composed of a copolymer of styrene-butadiene and unsaturated acid/ester units, which reduces cold press pressure and enhances adhesion, while minimizing binder usage and impedance.

Benefits of technology

The core-shell binder reduces the internal resistance of battery cells by 5-12%, increases the charging window, and improves adhesion without film or powdering, enhancing the dynamic performance of the battery cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502184000001_ABST
    Figure 2025502184000001_ABST
Patent Text Reader

Abstract

The present application relates to a binder, a binder composition, a preparation method, a negative electrode slurry, a negative electrode sheet, a secondary battery, a battery module, a battery pack, and an electric device, in which the binder includes a core material having a glass transition temperature of -50°C to 0°C and a shell material located on at least a part of the surface of the core material and having a glass transition temperature of 60°C to 100°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of secondary batteries, and in particular to a binder, a binder composition, a preparation method, a negative electrode slurry, a negative electrode sheet, a secondary battery, a battery module, a battery pack, and an electric device. [Background technology]

[0002] Due to their outstanding characteristics such as light weight, non-pollution, no memory effect, etc., secondary batteries are widely used in various consumer electronic products and electric vehicles. With the development of the new energy industry, clients have higher demands for secondary batteries.

[0003] In the related art, the binders styrene butadiene rubber and sodium carboxymethyl cellulose are often used to prepare the negative electrode sheet, but the processing performance of the negative electrode sheet and the dynamic performance of the battery cell corresponding to the negative electrode sheet cannot be combined. Therefore, the traditional binders used in the negative electrode sheet have room for improvement. Summary of the Invention [Problem to be solved by the invention]

[0004] In view of the problems existing in the background art, the present application provides a binder, a binder composition, a preparation method, a negative electrode slurry, a negative electrode sheet, a secondary battery, a battery module, a battery pack, and an electric device, which aim to simultaneously satisfy both the processing performance of a negative electrode sheet and the dynamic performance of a battery cell corresponding to the negative electrode sheet. [Means for solving the problem]

[0005] In order to achieve the above object, the first aspect of the present application is A core material with a glass transition temperature of -50℃ to 0℃; a shell material located on at least a part of the surface of the core material and having a glass transition temperature of 60° C. to 100° C.; A binder comprising:

[0006] Compared with the prior art, the present application has at least the following advantageous effects:

[0007] In the binder according to the present application, the shell material is located on at least a part of the surface of the core material, the core material being a flexible material with a low glass transition temperature, and the shell material being a hard material with a high glass transition temperature, the binder has a core-shell structure with a soft inside and a hard outside. The flexible core material is advantageous for cold pressing of the negative electrode sheet, which helps to reduce the cold pressing pressure, increases the compaction window of the negative electrode active material, and provides relatively good adhesion, and can further reduce the amount of binder used. The relatively small amount of binder used reduces the coverage on the surface of the negative electrode active material. The relatively hard shell material does not deform excessively after the negative electrode sheet is cold pressed, which reduces the coverage area of ​​the binder on the negative electrode active material, effectively reducing the impedance during the insertion and desorption of lithium ions, and improving the dynamic performance of the battery cell corresponding to the negative electrode sheet. In this way, when the binder is applied to a battery cell, the direct current internal resistance (DCR) of the battery cell is reduced by 5% to 12%, the charging window is slightly increased, and compared with the styrene-butadiene rubber used in the conventional technology, the adhesive strength of the binder in the present application is more than 20% higher, there is no peeling or powdering, and the interface at full charge is good.

[0008] In any embodiment of the present application, the shell material comprises a polar group.

[0009] In any embodiment of the present application, the core material includes a copolymer of styrene monomer units and butadiene monomer units.

[0010] In any embodiment of the present application, the shell material comprises a copolymer of styrene monomer units-butadiene monomer units-unsaturated acid monomer units-unsaturated ester monomer units.

[0011] In any embodiment of the present application, the monomer corresponding to the unsaturated acid monomer unit includes an unsaturated acid having a substituted or unsubstituted -C=C- and a carbon atom number of 3 to 6, Optionally, the monomers corresponding to the unsaturated acid monomer units include one or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid, and icoic acid.

[0012] In any embodiment of the present application, the monomer corresponding to the unsaturated ester monomer unit comprises a substituted or unsubstituted -C=C- containing unsaturated ester, Optionally, the monomer corresponding to the unsaturated ester monomer unit comprises one or more of methyl methacrylate, ethylhexyl ester, vinyl acetate, isooctyl acrylate, hydroxyethyl acrylate, isobornyl methacrylate, vinyl neodecanoate, butyl acrylate, acrylocyanide, ethyl acrylate, n-butyl acrylate, and isobutyl acrylate.

[0013] In any embodiment of the present application, the viscosity of an aqueous solution of the binder at 25° C. and a solid content of 45% is 10 mPa·s to 200 mPa·s.

[0014] In any embodiment of the present application, the binder has a volume average particle diameter Dv50 of 100 nm to 1000 nm.

[0015] A second aspect of the present application provides a method for preparing a binder comprising the steps of:

[0016] S11: A step of preparing the core material by polymerizing a styrene monomer and a butadiene monomer. S12: A step of polymerizing a styrene monomer, a butadiene monomer, an unsaturated acid monomer, and an unsaturated ester monomer on the surface of the core material. In any embodiment of the present application, in the polymerization reaction for preparing the core material, the mass ratio of the styrene monomer to the butadiene monomer is 10:(4 to 8).

[0017] In any embodiment of the present application, in the polymerization reaction for preparing the shell material, the mass ratio of the styrene monomer, the butadiene monomer, the unsaturated acid monomer, and the unsaturated ester monomer is 10:(4-8):(1-3):(2-4).

[0018] A third aspect of the present application provides a binder composition comprising the binder of the first aspect of the present application or the binder prepared by the method of the second aspect of the present application and high-viscosity sodium carboxymethylcellulose, wherein an aqueous solution of the high-viscosity sodium carboxymethylcellulose has a viscosity of 10,000 mPa s to 20,000 mPa s at a solids content of 1% at 25°C.

[0019] In any embodiment of the present application, the mass ratio of the binder to the high-viscosity sodium carboxymethylcellulose is (1.1 to 3.5:1).

[0020] In any embodiment of the present application, the hydrogen atom of the hydroxy group in the high viscosity sodium carboxymethylcellulose is replaced with a displacing agent, and the displacing agent and the hydroxy group react to form a hemiacetal; Optionally, the displacement agent comprises a dialdehyde monomer, and further optionally, the dialdehyde monomer comprises one or two of glyoxal and glutaraldehyde.

[0021] A fourth aspect of the present application provides an anode slurry comprising the binder of the first aspect of the present application, the binder prepared by the method of the second aspect of the present application, or the binder composition of the third aspect of the present application.

[0022] A fifth aspect of the present application provides a method for preparing a negative electrode slurry, the method comprising the steps of:

[0023] S21: preparing a negative electrode active material aggregate from a negative electrode active material, a portion of the high-viscosity sodium carboxymethylcellulose, a conductive agent, and a portion of a solvent; S22: Adding the remaining part of the high-viscosity sodium carboxymethylcellulose, the remaining part of the solvent, and the binder to the negative electrode active material agglomerates to prepare the negative electrode slurry.

[0024] In any embodiment of the present application, S201: A step of alkalizing cotton fibers and an alkalizing agent in a mixed solution of ethanol and water. S202: After the alkalinization reaction is completed, an etherification agent is added to the reaction system to perform an etherification reaction. S203: A step of displacing the product of the etherification reaction with a displacing agent to prepare the high-viscosity sodium carboxymethylcellulose. The method further comprises preparing the high viscosity sodium carboxymethylcellulose comprising: Optionally, the displacement agent comprises a dialdehyde monomer, and further optionally, the dialdehyde monomer comprises one or two of glyoxal and glutaraldehyde.

[0025] In any embodiment of the present application, step S203 satisfies at least one of the following conditions I to III.

[0026] I. The mass ratio of the product of the etherification reaction to the displacement agent is 100:(0.2-1.0). II. The temperature of the substitution reaction is 30°C to 70°C. III. The time for the substitution reaction is 20 minutes to 120 minutes.

[0027] A sixth aspect of the present application is A negative electrode current collector, and a negative electrode active material layer located on at least one surface of the negative electrode current collector; A negative electrode sheet comprising: The negative electrode active material layer contains the binder according to the first aspect of the present application, the binder prepared by the method according to the second aspect of the present application, or the binder composition according to the third aspect of the present application. A negative electrode sheet is provided.

[0028] In any embodiment of the present application, the mass ratio of the binder in the negative electrode active material layer is 1.3% to 2.1%, optionally 1.5% to 2.1%, and further optionally 1.8% to 2.1%.

[0029] In any embodiment of the present application, the negative electrode active material layer contains the binder composition of the third aspect of the present application, and the mass ratio of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer is 0.6% to 1.2%, optionally 0.8% to 1.2%, and further optionally 0.9% to 1.2%.

[0030] A seventh aspect of the present application provides a secondary battery including the negative electrode sheet of the sixth aspect of the present application.

[0031] An eighth aspect of the present application provides a battery module including the secondary battery of the seventh aspect of the present application.

[0032] A ninth aspect of the present application provides a battery pack including the battery module of the eighth aspect of the present application.

[0033] A tenth aspect of the present application provides an electric device including at least one of the secondary battery according to the seventh aspect of the present application, the battery module according to the eighth aspect of the present application, or the battery pack according to the ninth aspect of the present application.

[0034] In order to more clearly describe the technical solution of the present application, the following briefly describes the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can further obtain other drawings based on these drawings without creative efforts. [Brief description of the drawings]

[0035] [Figure 1] FIG. 1 is a viscosity-time curve of the negative electrode slurry in Example 23 of the present application. [Diagram 2] FIG. 2 is a graph showing the adhesive strength-time curve of the negative electrode sheet in Example 23 of the present application. [Diagram 3]FIG. 3 is a histogram of discharge DCR of the battery cells in Examples 24, 25, and 26 of the present invention and Comparative Example 7. [Figure 4] FIG. 4 is a schematic diagram of an embodiment of a secondary battery. [Diagram 5] FIG. 5 is an exploded view of FIG. [Figure 6] FIG. 6 is a schematic diagram of one embodiment of a battery module. [Figure 7] FIG. 7 is a schematic diagram of one embodiment of a battery pack. [Figure 8] FIG. 8 is an exploded view of FIG. [Figure 9] FIG. 9 is a schematic diagram of one embodiment of an apparatus that uses a secondary battery as a power source. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] The present application will now be further described with reference to specific embodiments, which should be understood as being merely illustrative of the present application and not limiting the scope of the present application.

[0037] The "ranges" disclosed herein are defined in the form of lower and upper limits, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any other upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Also, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4, and 5, then ranges such as 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all contemplated. In this application, unless otherwise stated, the numerical range "a-b" represents a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed herein, and "0-5" is simply shorthand for combinations of these numbers. Also, when a parameter is expressed as an integer ≧2, this is equivalent to disclosing that the parameter is an integer, e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] In the explanation of this specification, unless otherwise specified, "more than or equal to" and "less than or equal to" are inclusive of the number, and "multiple types" in "one type or multiple types" means two types or more than two types.

[0039] Unless otherwise specified, all the embodiments and optional embodiments in the present application can be combined with each other to form a new technical solution.

[0040] Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a novel technical solution.

[0041] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), which means that the method performs steps (a) and (b) in sequence, or performs steps (b) and (a) in sequence. For example, the method mentioned above may further include step (c), which means that step (c) may be added to the method in any order, for example, the method includes steps (a), (b) and (c), the method includes steps (a), (c) and (b), or the method includes steps (c), (a) and (b), etc.

[0042] Unless otherwise specified, the terms "comprise" and "contain" as used herein may be open ended or closed ended. For example, the terms "comprise" and "contain" may mean that other components not listed may also be included or contained, and may only include or contain the listed components.

[0043] Unless otherwise specified, the term "or" in this application is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or A and B are true (or exist). Unless otherwise specified, the terms used in this application have the well-known meanings that are commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of each parameter mentioned in this application can be measured by various measurement methods commonly used in the art (e.g., can be tested by the method used in the examples of this application).

[0044] In the related art, the binders styrene butadiene rubber and sodium carboxymethylcellulose are often used to prepare negative electrode sheets, but the processing performance of the negative electrode sheets and the dynamic performance of the battery cells cannot be combined. This is mainly because the technicians of the present application found that the negative electrode sheets prepared using the conventional binders styrene butadiene rubber with a usage percentage of 2% to 2.5% and the conventional binders hydroxymethylcellulose sodium with a usage percentage of 1% to 2% in the negative electrode active material layer have poor dynamic performance in high-power systems in the corresponding battery cells, and when the amount of styrene butadiene rubber and sodium hydroxymethylcellulose added is reduced to improve the dynamic performance of the battery cells, a series of processing problems such as settling due to the reduced viscosity of the negative electrode slurry, reduced filterability, scratches of the coating particles, and reduced adhesive strength of the negative electrode sheets are generated, which leads to further deterioration of the dynamic performance of the battery cells.

[0045] The binder provided in the present application includes a core material having a glass transition temperature of -50°C to 0°C, and a shell material located on at least a part of the surface of the core material and having a glass transition temperature of 60°C to 100°C.

[0046] Without being bound by any theory, the binder according to the present application has a shell material located on at least a portion of the surface of a core material, the core material being a flexible material with a lower glass transition temperature, and the shell material being a hard material with a higher glass transition temperature, so that the binder has a core-shell structure that is soft inside and hard outside. The flexible core material is advantageous for cold pressing of the negative electrode sheet, which helps to reduce the cold pressing pressure and increase the maximum pressed density window of the negative electrode active material, and also provides relatively good adhesion, and can reduce the amount of binder used. The relatively small amount of binder used reduces the coverage on the surface of the negative electrode active material. The relatively hard shell material does not deform excessively after cold pressing of the negative electrode sheet, reduces the coverage area of ​​the binder on the negative electrode active material, effectively reduces the impedance when lithium ions are inserted and extracted, and improves the dynamic performance of a battery cell corresponding to the negative electrode sheet. In this way, when the binder is applied to a battery cell, the direct current internal resistance (DCR) of the battery cell is reduced by 5% to 12%, the charging window is slightly increased, and compared with the styrene-butadiene rubber used in the conventional technology, the adhesive strength of the binder in the present application is increased by more than 20%, there is no peeling or powdering, and the interface at full charge is good.

[0047] It should be understood that the shell material may cover the entire surface of the core material or only a portion of the surface of the core material, but preferably covers the entire surface of the core material. The polar group may include one or more of a carboxyl group, a hydroxyl group, a carbonyl group, and an ester group.

[0048] The glass transition temperature of the core and shell materials mentioned before can be tested by differential scanning calorimetry (DSC), the specific steps are as follows: 1. Sample preparation: 1-3 mg of sample is weighed into an Al crucible, and the crucible lid is closed; 2. Parameter setting: nitrogen gas atmosphere, purge gas 50Ml / min, protective gas 100Ml / min; 3. Temperature increase sequence: 10℃ / min, 35℃~-30℃, 3min at -30℃, 10℃ / min, -30℃~50℃; 4. The temperature where the slope of the DSC curve is maximum is read as the glass transition temperature.

[0049] In the present examples, the glass transition temperature of the core material is −50° C. to 0° C., and may be, for example, −50° C. to −5° C., −50° C. to −10° C., −50° C. to −20° C., −50° C. to −30° C., −50° C. to −40° C., −30° C. to −0° C., or −30° C. to −10° C. The glass transition temperature of the shell material is 60° C. to 100° C., and may be, for example, 60° C. to 95° C., 65° C. to 90° C., 70° C. to 85° C., or 70° C. to 80° C.

[0050] As a result of extensive research, the present inventors have discovered that the binder of the present application can further improve the dynamic performance of a battery cell if it satisfies not only the above-mentioned set conditions but also one or more of the following conditions:

[0051] In some embodiments, the shell material has a polar group, which can adjust the swelling ability of the binder in the electrolyte, thereby providing the binder with a relatively high swelling property in the electrolyte, improving the lithium ion transmission channel, and further improving the dynamic performance of the battery cell; the polar group of the shell material can provide a hydrogen bonding effect, which can further increase the adhesion of the binder to the negative electrode active material, and improve the processing performance of the negative electrode sheet.

[0052] In some embodiments, the core material may include a copolymer of styrene-butadiene monomer units.

[0053] In some embodiments, the shell material may include a copolymer of styrene monomer units-butadiene monomer units-unsaturated acid monomer units-unsaturated ester monomer units.

[0054] The copolymer of styrene monomer unit-butadiene monomer unit-unsaturated acid monomer unit-unsaturated ester monomer unit refers to a copolymer consisting of a styrene monomer unit, a butadiene monomer unit, an unsaturated acid monomer unit and an unsaturated ester monomer unit. The copolymer contains a styrene monomer unit, a butadiene monomer unit, an unsaturated acid monomer unit and an unsaturated ester monomer unit, but the order of arrangement of the styrene monomer unit, the butadiene monomer unit, the unsaturated acid monomer unit and the unsaturated ester monomer unit in the copolymer is not limited, and it should be understood that the styrene monomer unit, the butadiene monomer unit, the unsaturated acid monomer unit and the unsaturated ester monomer unit in the copolymer may be arranged in any order.

[0055] Optionally, the monomer corresponding to the unsaturated acid monomer unit includes an unsaturated acid containing substituted or unsubstituted -C=C- and having 3 to 6 carbon atoms. "Substituted or unsubstituted" means that the unsaturated acid may be substituted or unsubstituted. When the unsaturated acid defined is substituted, it is understood that it is optionally substituted with a group acceptable in the art, including but not limited to a silyl group, a carbonyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, a carbamoyl group, a haloformyl group, a formyl group, a cyano group, an isocyanate group, a thiocyanate group, an isothiocyanate group, a hydroxy group, a trifluoromethyl group, a nitro group, or a halogen, and the above groups may be further substituted with a substituent acceptable in the art. Furthermore, optionally, the monomer corresponding to the unsaturated acid monomer unit includes one or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid, and iconic acid.

[0056] Optionally, the monomer corresponding to the unsaturated ester monomer unit includes a substituted or unsubstituted -C=C-containing unsaturated ester. "Substituted or unsubstituted" means that the unsaturated ester may be substituted or unsubstituted. When the defined unsaturated ester is substituted, it is understood that it is optionally substituted with a group acceptable in the art, including but not limited to a silyl group, a carbonyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, a carbamoyl group, a haloformyl group, a formyl group, a cyano group, an isocyanate group, a thiocyanate group, an isothiocyanate group, a hydroxy group, a trifluoromethyl group, a nitro group, or a halogen, and the above group may be further substituted with a substituent acceptable in the art. Further optionally, monomers corresponding to the unsaturated ester monomer units include one or more of methyl methacrylate, ethylhexyl ester, vinyl acetate, isooctyl acrylate, hydroxyethyl acrylate, isobornyl methacrylate, vinyl neodecanoate, butyl acrylate, acrylocyanide, ethyl acrylate, n-butyl acrylate, and isobutyl acrylate.

[0057] In some embodiments, the viscosity of an aqueous solution of the binder at 25° C. and a solids content of 45% is 10 mPa·s to 200 mPa·s, and may be, for example, 10 mPa·s to 150 mPa·s, 20 mPa·s to 150 mPa·s, 50 mPa·s to 100 mPa·s, or 80 mPa·s to 100 mPa·s, etc.

[0058] The viscosity of the aqueous solution of the binder at 25°C when the solid content is 45% mentioned above can be measured by the following method. That is, 500g of the aqueous solution of the binder with a solid content of 45% to be measured was weighed, stirred for 2h, and measured after the binder to be measured was completely and uniformly stabilized. Measurement temperature: 25±1°C, rotor and rotation speed used: 63# rotor, 12r / min, value taken at 6th minute, device number: DV-2TLV Brookfield viscometer. In some embodiments, the volume average particle diameter Dv50 of the binder is 100nm to 1000nm, and may be, for example, 100nm to 900nm, 200nm to 900nm, 300nm to 600nm, 400nm to 600nm, or 500nm to 600nm, etc.

[0059] The volume average particle size Dv50 refers to the particle size corresponding to 50% in the cumulative volume distribution. For example, Dv50 can be easily measured by a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer of Marvin Instruments Co., Ltd. in the UK, according to the GB / T 19077-2016 particle size distribution laser diffraction method.

[0060] The present embodiment further provides a method for preparing the binder, comprising the steps of:

[0061] S11: A step of preparing the core material by polymerizing a styrene monomer and a butadiene monomer. S12: A step of polymerizing a styrene monomer, a butadiene monomer, an unsaturated acid monomer, and an unsaturated ester monomer on the surface of the core material. In some embodiments, the weight ratio of styrene monomer to butadiene monomer in the polymerization reaction to prepare the core material is 10:(4-8), and may be, for example, 10:(4-7), 10:(5-8), or 10:(5-6), etc.

[0062] In some embodiments, the weight ratio of the styrene monomer, the butadiene monomer, the unsaturated acid monomer, and the unsaturated ester monomer in the polymerization reaction to prepare the shell material is 10:(4-8):(1-3):(2-4), such as 10:(4-7):(2-3):(2-3) or 10:(5-8):(1-2):(2-3).

[0063] In the examples of the present application, the polymerization reaction for preparing the core material and the polymerization reaction for preparing the shell material both require the participation of an emulsifier and an initiator.

[0064] Optionally, the emulsifier may comprise one or more of sodium alkyl sulfate, sodium alkyl sulfonate, sodium alkyl diphenyl ether disulfonate, ammonium alkyl phenol ether sulfate, alkyl phenol ether sulfosuccinic acid ester sodium salt, sodium p-styrene sulfonate, sodium 2-acrylamido-2,2-dimethylethane sulfonate, sodium allyl succinic acid alkyl ester sulfonate, sodium acrylamidoisopropyl sulfonate and alkyl acrylic acid-2-ethane sulfonate sodium salt.

[0065] Optionally, the initiator may include one or more of sodium persulfate, ammonium persulfate, and potassium persulfate.

[0066] An embodiment of the present application further provides a binder composition comprising the above binder or a binder prepared by the above method, and high-viscosity sodium carboxymethylcellulose, wherein an aqueous solution of the high-viscosity sodium carboxymethylcellulose at 25°C has a viscosity of 10,000 mPa·s to 20,000 mPa·s at a solid content of 1%, and may be, for example, 10,000 mPa·s to 19,000 mPa·s, 10,000 mPa·s to 15,000 mPa·s, 13,000 mPa·s to 17,000 mPa·s, or 15,000 mPa·s to 20,000 mPa·s, etc.

[0067] In the prior art, the sodium carboxymethylcellulose used in the negative electrode sheet has a viscosity of 2000 mPa·s to 8000 mPa·s when it is an aqueous solution with a solid content of 1% at 25°C. However, the aqueous solution of high-viscosity sodium carboxymethylcellulose with a solid content of 1% mentioned above has a significantly increased viscosity at 25°C. The use of high-viscosity sodium carboxymethylcellulose not only ensures the processing performance of the negative electrode sheet, but also allows the amount of sodium carboxymethylcellulose to be appropriately reduced, reduces the surface coverage of the negative electrode active material, reduces the transition impedance of lithium ions, and improves the dynamic performance of the battery cell corresponding to the negative electrode sheet.

[0068] The viscosity of the aqueous solution of the previously mentioned high-viscosity sodium carboxymethylcellulose at 25°C when the solid content is 1% can be measured by the following method: Weigh out 5.0g of the high-viscosity sodium carboxymethylcellulose to be measured with a dry weight of 500g, add pure water so that the total weight of the high-viscosity sodium carboxymethylcellulose to be measured and the pure water is 500g, dissolve it by stirring for 2 hours to completely and uniformly disperse the high-viscosity sodium carboxymethylcellulose to be measured, and then measure it. Different rotors correspond to different viscosities. Measurement temperature: 25±1°C, rotor and rotation speed used: 63# rotor, 12r / min, value taken at 6th minute, device number: DV-2TLV Brookfield viscometer.

[0069] In some embodiments, the mass ratio of the binder to the high-viscosity sodium carboxymethylcellulose is (1.1-3.5):1, and may be, for example, (1.1-3):1, (1.6-2.6):1, (1.8-2.2):1, or (2-2.2), etc. Through research by engineers, it has been discovered that when the mass ratio of the binder to the high-viscosity sodium carboxymethylcellulose is within this range, it contributes to further improving the adhesive strength of the binder composition.

[0070] In some embodiments, the hydrogen atom of hydroxyl group in high-viscosity sodium carboxymethylcellulose is replaced by a substitute, and the substitute reacts with hydroxyl group to generate hemiacetal.By replacing the hydrogen atom of hydroxyl group in high-viscosity sodium carboxymethylcellulose with a substitute, high-viscosity sodium carboxymethylcellulose temporarily loses hydrophilicity, avoiding the immediate sticky phenomenon that occurs when high-viscosity sodium carboxymethylcellulose contacts water, and favorable for the rapid dispersion of high-viscosity sodium carboxymethylcellulose in water.At the same time, hemiacetal can be hydrolyzed in the process of dissolving in water to generate hydroxyl group again, and recover hydrophilicity.

[0071] Optionally, the displacement agent may include a dialdehyde monomer, and further optionally, the dialdehyde monomer may include one or two of glyoxal and glutaraldehyde.

[0072] The present embodiment further provides a method for preparing high viscosity sodium carboxymethylcellulose, which includes the following steps:

[0073] S201: A step of alkalizing cotton fibers and an alkalizing agent in a mixed solution of ethanol and water. In some embodiments, the mass ratio of water to cotton fiber is (0.3-0.8):1, such as (0.3-0.7):1, (0.4-0.6):1, or (0.5-0.7):1. The mass ratio of ethanol to cotton fiber is (1.0-2.0):1, such as (1.0-1.8):1, (1.1-1.7):1, (1.3-1.6):1, or (1.4-1.5):1. The alkalizing agent may be a sodium hydroxide aqueous solution having a mass percent concentration of 30%-55%, and the mass ratio of the alkalizing agent to cotton fiber is (0.6-1.0):1, such as (0.6-0.9):1, (0.7-1.0):1, or (0.7-0.8):1. The time of the alkalizing reaction may be 30 min-80 min, and the temperature of the alkalizing reaction may be 10°C-40°C.

[0074] S202: After the alkalinization reaction is completed, an etherification agent is added to the reaction system to perform an etherification reaction. In some embodiments, the etherification agent may be an ethanol solution of chloroacetic acid with a mass percent concentration of 50% to 80%. The mass ratio of the etherification agent to the cotton fiber may be (1.0 to 1.5):1, such as (1.0 to 1.4):1 or (1.2 to 1.3):1. The time of the etherification reaction may be 40 min to 70 min, and the temperature of the etherification reaction may be 60°C to 90°C.

[0075] S203: A step of preparing the high viscosity carboxymethyl cellulose by subjecting the product of the etherification reaction to a substitution reaction with a substitution agent. Optionally, the displacement agent comprises a dialdehyde monomer, and further optionally, the dialdehyde monomer comprises one or two of glyoxal and glutaraldehyde.

[0076] In some embodiments, the mass ratio of the product of the etherification reaction to the displacement agent is 100:(0.2-1.0), and may be, for example, 100:(0.2-0.8), 100:(0.3-0.7), or 100:(0.4-0.6), etc.

[0077] In some embodiments, the temperature of the substitution reaction is 30°C to 70°C, and may be, for example, 30°C to 60°C, 40°C to 70°C, or 50°C to 60°C, etc.

[0078] In some embodiments, the duration of the substitution reaction is 20 min to 120 min, and may be, for example, 20 min to 110 min, 30 min to 90 min, 40 min to 70 min, or 50 min to 60 min, etc.

[0079] The present embodiment further provides an anode slurry comprising the binder described above, the binder prepared by the method described above, or the binder composition described above.

[0080] The present embodiment further provides a method for preparing an anode slurry, the method including the steps of: S21: preparing a negative electrode active material aggregate from a negative electrode active material, a portion of the high-viscosity sodium carboxymethylcellulose, a conductive agent, and a portion of a solvent; S22: Adding the remaining part of the high-viscosity sodium carboxymethylcellulose, the remaining part of the solvent, and the binder to the negative electrode active material agglomerates to prepare the negative electrode slurry.

[0081] In the embodiment of the present application, when preparing the negative electrode slurry, the high-viscosity sodium carboxymethylcellulose is added in two portions. First, in order to promote uniform dispersion of the negative electrode active material in the aqueous slurry, a part of the high-viscosity sodium carboxymethylcellulose is added to impregnate the negative electrode active material, and then the negative electrode active material is agglomerated by stirring and kneading. Finally, the remaining part of the high-viscosity sodium carboxymethylcellulose is added, and the negative electrode active material is agitated. The high-viscosity sodium carboxymethylcellulose can suspend and disperse the negative electrode active material. It is understood that the high-viscosity sodium carboxymethylcellulose can be rapidly dispersed in water, and therefore, compared with the sodium carboxymethylcellulose used in the traditional negative electrode slurry, it can shorten the agitation time, meet the 2h anode slurry agitation preparation process, and improve the agitation production capacity.

[0082] In some embodiments, the high-viscosity sodium carboxymethylcellulose is added in two portions, and the mass ratio of the high-viscosity sodium carboxymethylcellulose added in the first portion to the high-viscosity sodium carboxymethylcellulose added in the second portion is (0.25-1):1, and may be, for example, (0.25-0.9):1, (0.3-0.8):1, or (0.5-0.7):1, etc.

[0083] Negative electrode sheet The present embodiment provides a negative electrode sheet including a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, The present invention further provides a negative electrode sheet, in which the negative electrode active material layer comprises the above-mentioned binder, the negative electrode binder prepared by the above-mentioned method, or the above-mentioned binder composition.

[0084] In some embodiments, the mass ratio of the binder in the negative electrode active material layer is 1.3% to 2.1%, optionally 1.5% to 2.1%, and further optionally 1.8% to 2.1%. The amount of the binder used in the negative electrode active material layer is obviously lower than the amount of the binder styrene butadiene rubber used in the prior art.

[0085] The mass ratio of the binder in the negative electrode active material layer mentioned above can be measured by the following method: First, the mass M1 of the binder in the negative electrode active material layer is measured, and then the mass M0 of the negative electrode active material layer is measured, and the mass ratio of the binder in the negative electrode active material layer is calculated according to the formula M1 / M0*100%.

[0086] In some embodiments, the negative electrode active material layer includes the binder composition, and the mass ratio of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer is 0.6% to 1.2%, optionally 0.8% to 1.2%, and further optionally 0.9% to 1.2%. The mass ratio of the sodium carboxymethylcellulose in the negative electrode active material layer adopted in the prior art is usually 1% to 2%, but the mass ratio of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer of the embodiments of the present application is clearly reduced.

[0087] The mass ratio of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer mentioned above can be measured by the following method: First, the mass M2 of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer is measured, and then the mass M0 of the negative electrode active material layer is measured, and the mass ratio of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer is calculated according to the formula M2 / M0*100%.

[0088] The negative electrode current collector may be a normal metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate (e.g., a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) etc.).

[0089] The negative electrode active material layer usually contains a negative electrode active material, a conductive agent, and any other auxiliary agents.

[0090] For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may be at least one selected from silicon alone, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy. The tin-based material may be at least one selected from tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other traditional materials used as negative electrode active materials in batteries may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0091] By way of example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0092] By way of example, the other optional auxiliary material may be a PTC thermistor material, and the like.

[0093] For example, the negative electrode sheet can be prepared in the following manner: The components for preparing the negative electrode sheet described above, such as the negative electrode active material, conductive agent, binder, and other optional components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then applied onto a negative electrode current collector, and the negative electrode sheet can be obtained through processes such as drying and cold rolling.

[0094] All of the above raw materials are commercially available unless otherwise specified.

[0095] secondary battery A secondary battery refers to a battery that can be used continuously by activating the active material through charging after discharging the battery.

[0096] In general, a secondary battery includes a positive electrode sheet, the above-described negative electrode sheet according to the present application, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions are repeatedly inserted and removed between the positive electrode sheet and the negative electrode sheet. The separator is provided between the positive electrode sheet and the negative electrode sheet to serve as an insulator. The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet.

[0097] Positive electrode sheet In a secondary battery, the positive electrode sheet usually includes a positive electrode current collector and a positive electrode membrane layer containing a positive electrode active material provided on at least one surface of the positive electrode current collector.

[0098] For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is provided on either one or both of the two opposing surfaces of the positive electrode current collector.

[0099] For example, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate (e.g., a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0100] When the secondary battery is a lithium ion battery, the positive electrode active material may be a positive electrode active material for lithium ion batteries known in the art. For example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials used as battery positive electrode active materials may be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (also abbreviated as LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (also abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (also abbreviated as LiNi 0.6 Co 0.2 Mn 0.2O2(NCM 622 (also abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (also abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0101] When the secondary battery is a sodium ion battery, the positive electrode active material may be a positive electrode active material for sodium ion batteries known in the art. For example, the positive electrode active material may be used alone or in combination of two or more. Among them, the positive electrode active material may be sodium iron composite oxide (NaFeO2), sodium cobalt composite oxide (NaCoO2), sodium chromium composite oxide (NaCrO2), sodium manganese composite oxide (NaMnO2), sodium nickel composite oxide (NaNiO2), sodium nickel titanium composite oxide (NaNi 1 / 2 Ti 1 / 2 O2), sodium nickel manganese composite oxide (NaNi 1 / 2 Mn 1 / 2 O2), sodium iron manganese oxide (Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2), sodium nickel cobalt manganese composite oxide (NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), sodium iron phosphate (NaFePO4), sodium manganese phosphate (NaMn PO4), sodium cobalt phosphate compounds (NaCoPO4), Prussian blue-based materials, polyanion materials (phosphates, fluorophosphates, pyrophosphates, sulfates), etc., but the present application is not limited to these materials and other traditional materials used as positive electrode active materials in sodium ion batteries may also be used.

[0102] The positive electrode membrane layer may typically optionally contain a binder, a conductive agent, and other optional auxiliary agents.

[0103] For example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0104] By way of example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0105] For example, the positive electrode sheet can be manufactured in the following manner: The components for manufacturing the positive electrode sheet described above, for example, the positive electrode active material, conductive agent, binder, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied onto a positive electrode current collector, and the positive electrode sheet can be obtained through processes such as drying and cold rolling.

[0106] Separator In some embodiments, the secondary battery further includes a separator. The present application does not particularly limit the type of separator, and any known porous structure separator having good chemical stability and mechanical stability can be selected.

[0107] In some embodiments, the separator may be made of at least one material selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, and there is no particular restriction. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and there is no particular restriction.

[0108] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be fabricated into an electrode assembly by a winding or lamination process.

[0109] electrolyte The secondary battery may include an electrolyte, which serves to conduct ions between the positive electrode and the negative electrode. The electrolyte may include an electrolyte salt and a solvent.

[0110] By way of example, the electrolyte salt may be one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiDFOB), lithium difluoro(oxalato)borate (LiBOB), lithium bis(oxalato)borate (LiPO2F2), lithium difluorobis(oxalato)phosphate (LiDFOP), and lithium tetrafluoro(oxalato)phosphate (LiTFOP).

[0111] By way of example, the solvent may comprise one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0112] In some embodiments, the electrolyte may further include additives. For example, the additives may include a negative electrode film-forming additive, a positive electrode film-forming additive, or an additive that can improve certain performance of the battery, such as an additive that improves the overcharge performance of the battery, or an additive that improves the high-temperature and low-temperature performance of the battery.

[0113] In some embodiments, the secondary battery according to the present application is a lithium ion secondary battery.

[0114] The secondary battery can be manufactured according to conventional methods in the art, for example, by sequentially winding (or stacking) a positive electrode sheet, a separator, and a negative electrode sheet, with the separator positioned between the positive electrode sheet and the negative electrode sheet to act as an insulator, to obtain a battery cell, placing the battery cell in an exterior case, injecting an electrolyte, and sealing the opening to obtain a secondary battery.

[0115] In the present embodiment, the shape of the secondary battery is not particularly limited, and it may be cylindrical, rectangular or any other shape. For example, FIG. 4 shows a secondary battery 5 having a rectangular structure as an example.

[0116] In some embodiments, the secondary battery may include an exterior case that is used to seal the electrode assembly and the electrolyte.

[0117] In some embodiments, the exterior of the secondary battery may be a hard case such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft bag such as a pouch-type soft bag, etc. The material of the soft bag may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0118] 5, in some embodiments, the exterior may include a case 51 and a cover plate 53. The case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate may be surrounded to form a receiving cavity. The case 51 may have an opening communicating with the receiving cavity, and the cover plate 53 may cover the opening to close the receiving cavity.

[0119] The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is sealed in the aforementioned receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 can be one or more and can be adjusted according to needs.

[0120] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0121] 6 shows an example of a battery module 4. In the battery module 4, the secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the secondary batteries 5 may be fixed by fasteners.

[0122] Optionally, the battery module 4 may include a housing having an accommodation space for accommodating a plurality of secondary batteries 5 .

[0123] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0124] 7 and 8 show an example battery pack 1. The battery pack 1 may include a battery housing and a plurality of battery modules 4 provided in the battery housing. The battery housing includes an upper housing 2 and a lower housing 3, and the upper housing 2 can be fitted over the lower housing 3 and forms an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in any manner within the battery housing.

[0125] Electrical equipment The present application further provides an electric device comprising at least one of the secondary battery, battery module or battery pack. The secondary battery, battery module or battery pack may be used as a power source for the device, or may be used as an energy storage unit for the device. The device may be, but is not limited to, a mobile device (e.g., mobile phone, laptop, etc.), an electric vehicle (e.g., pure electric vehicle, hybrid electric vehicle, plug-in hybrid electric vehicle, electric bicycle, electric scooter, electric golf cart, electric truck, etc.), a train, a ship and a satellite, an energy storage system, etc.

[0126] The device can select a secondary battery, a battery module or a battery pack according to its usage needs.

[0127] 9 is an example of an electric device 6. The electric device 6 may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module may be adopted to meet the high power and high energy density requirements of the lithium-ion battery of the device.

[0128] Another example of the electric device may be a mobile phone, a tablet, a notebook computer, etc. Such devices are usually required to be thin, and may employ a secondary battery as a power source.

[0129] The beneficial effects of the present invention will be further illustrated below with reference to examples. EXAMPLES

[0130] In order to make the problems, technical solutions and beneficial effects of the present application clearer, the present application will be described in more detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only some of the embodiments of the present application, but not all of the embodiments. The description of at least one exemplary embodiment below is merely illustrative in nature, and does not limit the present application and its application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without any creative effort are within the scope of protection of the present application.

[0131] All materials used in the examples herein are commercially available.

[0132] 1. Preparation of binder Example 1: The binder contained a core material and a shell material that covered the surface of the core material. The glass transition temperature of the core material was -30°C, the glass transition temperature of the shell material was 80°C, the viscosity of the binder aqueous solution at 25°C when the solid content was 1% was 100 mPa·s, and the volume average particle diameter Dv50 of the binder was 500 nm. Specifically, the preparation method was as follows.

[0133] 1) 110g of water, 0.65g of initiator, 1.5g of emulsifier were added to a reaction kettle, and then 50g of styrene and 25g of butadiene were added. The pH value was adjusted to 5, and the reaction kettle was heated to 70°C and reacted for 40 minutes to prepare a core layer emulsion containing a core material.

[0134] 2) 50 g of styrene, 25 g of butadiene, 10 g of methacrylic acid, and 15 g of methyl methacrylate were added dropwise to a reaction kettle, and then 1.5 g of emulsifier, 0.65 g of initiator, and 110 g of deionized water were added dropwise. After thorough stirring for 1.5 hours, the reaction kettle was heated to 80°C and reacted with stirring for 6 hours. Then, the reaction was cooled, and the product was recovered to prepare an emulsion containing a binder.

[0135] Examples 2 to 14: Examples 2 to 14 were basically the same as Example 1, but differed in at least one of the parameters, such as the type and / or amount of monomer used when preparing the core material, the type and / or amount of monomer used when preparing the shell material, the glass transition temperature of the core material, the glass transition temperature of the shell material, the viscosity of the aqueous solution of the binder at 25°C when the solid content is 1%, and the volume average particle diameter Dv50 of the binder, and the details are shown in Table 1 below.

[0136] Among them, in Examples 2 to 3, the reaction kettle pH value in step 1), the reaction kettle temperature and reaction time, and / or the reaction kettle temperature in step 2) were further adjusted.

[0137] Specifically, in Example 2, the pH value of the reaction kettle in step 1) was 4.5, the reaction kettle temperature was 60°C, the reaction time was 50 min, and the reaction kettle temperature in step 2) was 85°C.

[0138] Specifically, in Example 3, the pH value of the reaction kettle in step 1) was 5.5, the reaction kettle temperature was 80°C, the reaction time was 30 min, and the reaction kettle temperature in step 2) was 83°C.

[0139] Comparative Example 1 In Comparative Example 1, only the core material was prepared, and the binder of Comparative Example 1 was obtained by the same preparation method as in step 1) in Example 1.

[0140] Comparative Example 2 In Comparative Example 2, the shell material was directly prepared, and the binder of Comparative Example 2 was obtained by the same preparation method as step 2) in Example 1.

[0141] Comparative Examples 3 to 4 Comparative Examples 3 and 4 were basically the same as Example 1, except for the amount of monomer used in preparing the shell material, the details of which are shown in Table 1 below.

[0142] Binder Performance Test The solid content of the binder-containing emulsion in Examples 1 to 14 and Comparative Examples 1 to 4 was calculated. As a specific method, the total mass W1 of all materials other than deionized water added during the preparation process, and the total mass W2 of all materials including deionized water added during the preparation process were calculated, and the solid content of the binder contained in the emulsion was calculated according to the formula W1 / W2*100%.

[0143] The core material glass transition temperature, shell material glass transition temperature, viscosity of the binder aqueous solution at 25°C when the solid content is 1% and volume average particle diameter Dv50 of the binder in Examples 1 to 14 and Comparative Examples 1 to 4 were tested, and Dv50 represents the particle diameter corresponding to when the binder cumulative volume distribution percentage reaches 50%. The test methods were as follows: Core material glass transition temperature: The glass transition temperature of the core material was tested by differential scanning calorimetry (DSC), and the specific steps were as follows: 1. Sample preparation: 1-3 mg of core material was weighed into an Al crucible, and the crucible cover was closed. 2. Parameter settings: nitrogen gas atmosphere, purge gas 50Ml / min, protective gas 100Ml / min. 3. Temperature rise sequence: 10℃ / min, 35℃~-30℃, 3min at -30℃, 10℃ / min, -30℃~50℃. 4. The temperature at which the slope of the DSC curve is maximum was read as the glass transition temperature of the core material.

[0144] Shell material glass transition temperature: The glass transition temperature of the shell material was tested by differential scanning calorimetry (DSC), and the specific steps were as follows: 1. Sample preparation: 1-3 mg of shell material was weighed into an Al crucible, and the crucible lid was closed. 2. Parameter settings: nitrogen gas atmosphere, purge gas 50Ml / min, protective gas 100Ml / min; 3. Temperature rise sequence: 10℃ / min, 35℃~-30℃, 3min at -30℃, 10℃ / min, -30℃~50℃; 4. The temperature at which the slope of the DSC curve was maximum was read as the glass transition temperature of the shell material.

[0145] Viscosity of emulsion containing binder at 25℃: 500g of the emulsion containing the binder to be measured was weighed, and the binder to be measured was dissolved completely and uniformly by stirring for 2 hours, and then the measurement was performed. Measurement temperature: 25±1℃, rotor and rotation speed used: 63# rotor, 12r / min, and the value was taken at the 6th minute; Device number: DV-2TLV Brookfield viscometer.

[0146] Volume average particle diameter Dv50: GB / T 19077-2016 Particle size distribution was measured using a laser particle size analyzer (e.g., Mastersizer 2000E type laser particle size analyzer) in accordance with the laser diffraction method.

[0147] Some of the parameters of the binders prepared in Examples 1 to 14 and Comparative Examples 1 to 4, the types and amounts of monomers used in preparing the core material, and the types and amounts of monomers used in preparing the shell material are shown in Table 1 below.

[0148] [Table 1-1] [Table 1-2] [Table 1-3]

[0149] In Table 1, Tg1 indicates the glass transition temperature of the core material, and Tg2 indicates the glass transition temperature of the shell material. The viscosity indicates the viscosity of an aqueous solution of the binder with a solid content of 1% at 25°C.

[0150] 2. Preparation of high viscosity sodium carboxymethylcellulose Example 15: 1) The cotton fiber is crushed, the crushed cotton fiber is mixed with ethanol and water and added to a reactor, and then a sodium hydroxide aqueous solution is added. After the addition is completed, the air in the reactor is discharged so that the vacuum degree of the reactor is -0.08MPa, and inert gas is charged into the reactor so that the internal pressure of the reactor exceeds 0.02MPa. The process of evacuating and charging the inert gas is repeated 2 to 3 times to remove the air in the reactor, and the mixture is alkalized while stirring for 70 minutes. The alkalization temperature is 30°C, in which the mass ratio of water to cotton fiber is 0.5:1, the mass ratio of ethanol to cotton fiber is 1.5:1, the mass percentage concentration of the sodium hydroxide aqueous solution is 40%, and the mass ratio of the sodium hydroxide aqueous solution to cotton fiber is 0.8:1.

[0151] 2) The ethanol solution of chloroacetic acid was uniformly sprayed into the reactor, the air in the reactor was discharged until the reactor vacuum degree was -0.08MPa, and the inert gas was filled into the reactor until the reactor internal pressure exceeded 0.02MPa. The temperature of the reactor was increased to 80°C, and the etherification reaction was carried out for 50 minutes, in which the mass percentage concentration of the ethanol solution of chloroacetic acid was 70%, and the mass ratio of the ethanol solution of chloroacetic acid to cotton fiber was 1.2:1.

[0152] 3) After the etherification reaction is completed, the material is cooled to 50℃, added to alcohol with a volume concentration of 60%, adjusted to neutral pH with hydrochloric acid, washed twice, centrifuged twice, and then dried in a vacuum rake dryer. The moisture content of the material is measured to be 33%. An alcohol solution of glyoxal is sprayed evenly and added. The alcohol used is alcohol with a volume concentration of 65%. The temperature is controlled at 55℃ and the substitution reaction is carried out for 60 minutes. The residual alcohol is recovered under vacuum negative pressure (-0.02MPa). After post-treatment such as drying and pulverization, high-viscosity sodium carboxymethylcellulose is obtained, of which the mass ratio of the product after the etherification reaction to glyoxal is 100:0.6.

[0153] Examples 16 to 20 Examples 16 to 20 were basically the same as Example 15, but differed in that at least one of the following was different in step 1): the amount of ethanol used, the amount of water used, the concentration of the aqueous sodium hydroxide solution, the amount of the aqueous sodium hydroxide solution used, the alkalinization reaction time, the alkalinization reaction temperature, and / or the concentration of the ethanol solution of chloroacetic acid used in step 2), the amount of the ethanol solution of chloroacetic acid used, the etherification reaction time, the etherification reaction temperature, and / or the type and / or amount of the displacement agent used in step 3), the displacement reaction time, and the displacement reaction temperature. Details are shown in Table 2 below.

[0154] Example 21 Example 21 differs from Example 15 in that only the alkalization reaction and the etherification reaction were carried out, and no substitution reaction was carried out, and the alkalization reaction was carried out according to the same alkalization method as step 1) in Example 15, and the etherification reaction was carried out according to the same etherification method as step 2) in Example 15. The details are shown in Table 2 below.

[0155] High Viscosity Sodium Carboxymethylcellulose Performance Test The viscosity of the aqueous solutions of the high-viscosity sodium carboxymethylcellulose in Examples 15 to 21 at 25° C. and a solid content of 1% was tested. The test method was as follows.

[0156] Weigh out 5.0g of the high viscosity sodium carboxymethylcellulose to be measured, add pure water so that the total weight of the high viscosity sodium carboxymethylcellulose to be measured and the pure water is 500g, dissolve under stirring for 2 hours to completely and uniformly disperse the high viscosity sodium carboxymethylcellulose to be measured, and then measure. Different rotors correspond to different viscosities. Measurement temperature: 25±1℃, rotor and rotation speed used: 63# rotor, 12r / min, value taken at 6min; device number: DV-2TLV Brookfield viscometer.

[0157] The viscosities of the high-viscosity sodium carboxymethylcellulose prepared in Examples 15 to 20 and Comparative Examples 5 to 6, as well as the amounts used and parameter settings in the preparation process, are shown in Table 2 below.

[0158] [Table 2]

[0159] In Table 2, the viscosity refers to the viscosity of an aqueous solution of high-viscosity sodium carboxymethylcellulose having a solid content of 1% at 25°C.

[0160] 2. Preparation of negative electrode slurry Example 22: 95.9 g of graphite as a negative electrode active material, 0.16 g of high-viscosity sodium carboxymethylcellulose prepared in Example 15, and 2.0 g of carbon black (SP) as a conductive agent were mixed and stirred uniformly at 200 rpm for 15 minutes, 43.54 g of deionized water was added, and the mixture was stirred and kneaded at a rotation speed of 300 rpm for 60 minutes to obtain well-impregnated graphite agglomerates, 0.64 g of high-viscosity sodium carboxymethylcellulose was added, and the mixture was stirred at a rotation speed of 300 rpm for 5 minutes, and 43.54 g of deionized water was added, followed by dispersion at a rotation speed of 1200 rpm for 60 minutes, and 2.89 g of the binder-containing emulsion prepared in Example 1 was added, and the mixture was stirred at 800 rpm for 30 minutes to obtain a negative electrode slurry.

[0161] Examples 23 to 32 and Examples 34 to 56 Examples 23 to 32 and Examples 34 to 56 were basically the same as Example 21, but differed in at least one of the amount of negative electrode active material used, the type and / or amount of binder used, and the type and / or amount of high-viscosity sodium carboxymethylcellulose used, the details of which are shown in Table 3 below.

[0162] Example 33 Example 33 differs from Example 22 in that a 2h stirring process is adopted, and the details of the preparation process are as follows:

[0163] 95.9 g of graphite as a negative electrode active material, 0.16 g of high-viscosity sodium carboxymethylcellulose, and 2.0 g of carbon black as a conductive agent were mixed and stirred at 200 rpm for 5 minutes, and then 43.54 g of deionized water was added and stirred and kneaded at a rotation speed of 800 rpm for 30 minutes to obtain well-impregnated graphite agglomerates. 0.64 g of high-viscosity sodium carboxymethylcellulose was further added and stirred at a rotation speed of 300 rpm for 5 minutes, and 43.54 g of deionized water was added, and then dispersed at a rotation speed of 1200 rpm for 50 minutes. 4.0 g of binder-containing emulsion was added and stirred at 800 rpm for 30 minutes to obtain a negative electrode slurry, in which the solid content of the binder-containing emulsion was 45%.

[0164] Comparative Examples 7 to 11 Comparative Examples 7 to 11 were basically the same as Example 22, but differed in at least one of the amount of negative electrode active material used, the type and / or amount of binder used, and the type and / or amount of high-viscosity sodium carboxymethylcellulose used, and the details are shown in Table 3 below.

[0165] Anode Slurry Performance Test A slurry stability test was carried out on the negative electrode slurries prepared in Examples 22 to 56 and Comparative Examples 7 to 11, and the specific test process is shown below.

[0166] At 25°C, the shipping viscosity of the negative electrode slurry was adjusted to the application specification of 3,000 to 20,000 mPa.s, after which 500 mL of the slurry was taken out and left to stand. The viscosity of the negative electrode slurry was measured every 4 hours, and the amount of settling of the main material at the bottom of the slurry was measured every 12 hours by scraping it off with a steel plate, and measurement was stopped 24 hours after completion of measurement.

[0167] The viscosity-time curve of the negative electrode slurry in Example 23 is shown in Figure 1, where the horizontal axis is the test time and the vertical axis is the viscosity value of the negative electrode slurry. As can be seen from Figure 1, when the negative electrode slurry was left to stand for 24 hours, the viscosity of the negative electrode slurry hardly changed, indicating that the viscosity stability of the negative electrode slurry is good.

[0168] Table 3 shows the parameter settings for the preparation process of the negative electrode slurries in Examples 22 to 56 and Comparative Examples 7 to 11 and the results of the slurry stability tests.

[0169] [Table 3-1] [Table 3-2] [Table 3-3]

[0170] Here, in Table 3, high viscosity CMC refers to high viscosity sodium carboxymethylcellulose, and general-purpose CMC refers to general-purpose sodium carboxymethylcellulose. The general-purpose process refers to the negative electrode slurry preparation process adopted in Example 22, and the 2h stirring process refers to the negative electrode slurry preparation process adopted in Example 33. The viscosity of the general-purpose CMC was 5000 mPa s.

[0171] 3. Preparation of negative electrode sheet The negative electrode slurries in Examples 22 to 56 and Comparative Examples 7 to 11 were each uniformly applied to a copper foil as a negative electrode current collector, with the weight per side being 60 to 80 mg / 1540.25 mm 2The mixture was then dried, cold pressed, and slittered to obtain a negative electrode sheet.

[0172] Negative electrode sheet performance test A sheet adhesive strength test was carried out on each of the negative electrode sheets in Examples 22 to 56 and Comparative Examples 7 to 11, and the results of the adhesive strength tests are shown in the following Table 4. The specific test method was as follows.

[0173] At 25°C, take the negative electrode sheet as a test sheet, cut a sheet sample with a width of 30 mm and a length of 100 to 160 mm with a blade, attach a special double-sided tape to a steel plate, the tape is 20 mm wide and 90 to 150 mm long, attach the cut sheet sample to the double-sided tape with the test surface facing down, roll it three times in the same direction with a press roller, insert a paper tape with the same width as the sheet sample and a length 80 to 200 mm longer than the length of the sheet sample under the sheet sample and fix it with a wrinkle glue, turn off the power of the tension machine, Insert the plug, turn on the light, adjust the limit block to the appropriate position, fix the end of the steel plate that is not attached with the sheet sample with the lower jig, fold the paper tape up and fix it with the upper jig, adjust the position of the upper jig using the "up" and "down" buttons on the manual controller attached to the tension machine, open the dedicated computer linked to the tension machine, double-click the software icon on the desktop to perform the test, the tensile speed is 50m / min, the test distance is 50mm, and the software takes data points every 10 seconds.

[0174] The adhesive strength of the negative electrode sheet in Example 23 was tested three times in parallel. The adhesive strength-time curve of the negative electrode sheet in Example 23 is shown in Figure 2. The vertical axis is adhesive strength, and the horizontal axis is test distance. As can be seen from Figure 2, the average adhesive strength of the negative electrode sheet in Example 23 tested three times was higher than 15 N / m, indicating that the adhesive strength of the negative electrode sheet was good.

[0175] 4. Battery cell manufacturing 1. Preparation of positive electrode sheet: LiNi, the positive electrode active material 0.8 Co0.1 Mn 0.1 O2 (NCM811), polyvinylidene fluoride (PVDF) as a binder, and acetylene black as a conductive agent were dissolved in N-methylpyrrolidone (NMP) as a solvent in a mass ratio of 97%:1.5%:1.5%, and mixed thoroughly to form a positive electrode slurry. The positive electrode slurry was then uniformly applied to aluminum foil as a positive electrode current collector, and then dried, cold pressed, and slitted to obtain a positive electrode sheet.

[0176] 2. Separator: A polyethylene film (PE) with a thickness of 12 μm was used as the separator.

[0177] 3. Preparation of electrolyte: Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte, the concentration of LiPF6 in the electrolyte being 1 mol / L.

[0178] 4. Preparation of battery cells: The above positive electrode sheet, separator, negative electrode sheets prepared in Examples 22 to 56 and Comparative Examples 7 to 11, and electrolyte were assembled into a small soft bag battery cell.

[0179] Battery Cell Performance Test A battery direct current impedance test was carried out on the battery cells prepared in Examples 22 to 56 and Comparative Examples 7 to 11, and the specific test procedure was as follows.

[0180] At 25°C, the battery corresponding to Example 1 was charged to 4.2V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage of 4.2V, left for 5 minutes, and then discharged for 12 minutes at a constant current of 1C, and the voltage V1 was recorded. After being left for 5 minutes, the battery was left at -10°C for 2 hours, and then discharged for 10 seconds at 15C, and the voltage V2 was recorded, and (V2-V1) / 15C was obtained as the DCR of the battery cell.

[0181] The increase ratio of the battery cell internal resistance of the battery cells in Examples 22 to 56 and Comparative Examples 7 to 11 was calculated based on the DCR of the battery cell in Comparative Example 7. Taking Example 22 as an example, the increase ratio of the battery cell internal resistance in Example 22 = DCR (Example 22) / DCR (Comparative Example 7) * 100%, and the calculation method of the increase ratio of the battery cell internal resistance of the other Examples was the same as above. The results of the increase ratio of the battery cell internal resistance of the battery cells in Examples 22 to 56 and Comparative Examples 7 to 11 are shown in Table 4 below.

[0182] 3 shows the discharge DCR histograms of the battery cells in Examples 24, 25, 26 and Comparative Example 7. As can be seen from FIG. 3, the DCR of the battery cells was obviously reduced, indicating that the dynamic performance of the battery cells was significantly improved.

[0183] The performance test results of the negative electrode sheets and the battery cell performance test results of Examples 22 to 56 and Comparative Examples 7 to 11 are shown in Table 4 below.

[0184] [Table 4-1] [Table 4-2]

[0185] Here, in Table 4, the weight of the negative electrode excluding the tear weight indicates the weight per unit area of ​​the negative electrode sheet.

[0186] As can be seen from Example 1 and Comparative Examples 3-4 in Table 1, by optimizing the amounts of unsaturated acid monomer and unsaturated ester monomer used in preparing the shell material of the binder, the glass transition temperature of the shell material could be made within the required range of the binder.

[0187] As can be seen from Examples 39 and Comparative Examples 7 to 11 in Tables 1 to 4, by providing the binder of the present invention in the negative electrode active material layer of the negative electrode sheet, the sheet adhesive strength of the negative electrode sheet was increased, the processing performance of the negative electrode sheet was satisfied, and the DC internal resistance of the battery cell was reduced, thereby improving the dynamic performance of the battery cell.

[0188] As can be seen from Examples 22 to 38 and Examples 40 to 56, by simultaneously providing the binder of the present invention and high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer of the negative electrode sheet, the sheet adhesive strength of the negative electrode sheet was further increased, the processing performance of the negative electrode sheet was satisfied, the DC internal resistance of the battery cell was further reduced, and the dynamic performance of the battery cell was further improved. In particular, by further optimizing the amounts of the binder and high-viscosity sodium carboxymethylcellulose used in the negative electrode active material layer of the present invention, higher sheet adhesive strength and lower DC internal resistance of the battery cell were obtained.

[0189] The difference between Examples 22 to 25 and Examples 35 to 36 is that the mass percentage of the binder in the negative electrode active material layer is different. Preferably, the mass percentage of the binder is 1.3% to 2.1%. In this case, the negative electrode sheet has good processing performance and the battery cell has excellent dynamic performance. More preferably, the mass percentage of the binder is 1.5% to 2.1%, and even more preferably, the mass percentage of the binder is 7.8% to 2.1%.

[0190] The difference between Examples 26 to 33 and Examples 37 to 38 is that the mass proportion of high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer is different. Preferably, the mass proportion of high-viscosity sodium carboxymethylcellulose is 0.6% to 1.0%. In this case, the negative electrode sheet has good processing performance and the battery cell has excellent dynamic performance. More preferably, the mass proportion of high-viscosity sodium carboxymethylcellulose is 0.6% to 1.0%, and even more preferably, the mass proportion of high-viscosity sodium carboxymethylcellulose is 0.9% to 1.0%.

[0191] The difference between Example 24 and Example 33 is that the stirring process is different. The binder of the embodiment of the present application and high-viscosity sodium carboxymethylcellulose are used to prepare the negative electrode slurry, which can meet the 2-h stirring preparation process of the negative electrode slurry and improve the stirring production capacity.

[0192] The above are only specific embodiments of the present application, and the scope of protection of the present application is not limited thereto, and those skilled in the art can easily think of various equivalent modifications or replacements within the scope of the technology disclosed in the present application, and these modifications or replacements should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be subject to the scope of protection of the claims. [Explanation of symbols]

[0193] 1 Battery pack 2 Upper case 3 Lower case 4 Battery Module 5 Secondary battery 51 cases 52 Electrode Assembly 53 Lid plate 6 Electrical equipment.

Claims

1. A core material having a glass transition temperature of −50° C. to 0° C.; a shell material located on at least a part of the surface of the core material and having a glass transition temperature of 60° C. to 100° C.; A binder including:

2. The binder of claim 1 , wherein the shell material comprises a polar group.

3. 3. The binder according to claim 1, wherein the core material contains a copolymer of a styrene monomer unit and a butadiene monomer unit.

4. 4. The binder according to claim 1, wherein the shell material comprises a copolymer of styrene monomer units, butadiene monomer units, unsaturated acid monomer units and unsaturated ester monomer units.

5. The monomer corresponding to the unsaturated acid monomer unit includes an unsaturated acid having a substituted or unsubstituted -C=C- and having 3 to 6 carbon atoms; 5. The binder of claim 4, wherein optionally the monomers corresponding to the unsaturated acid monomer units include one or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid, and icoic acid.

6. Monomers corresponding to the unsaturated ester monomer units include substituted or unsubstituted -C=C-containing unsaturated esters, 6. The binder of claim 4 or 5, wherein optionally the monomer corresponding to the unsaturated ester monomer unit comprises one or more of methyl methacrylate, ethylhexyl ester, vinyl acetate, isooctyl acrylate, hydroxyethyl acrylate, isobornyl methacrylate, vinyl neodecanoate, butyl acrylate, acrylocyanide, ethyl acrylate, n-butyl acrylate, and isobutyl acrylate.

7. 7. The binder according to claim 1, wherein an aqueous solution of the binder has a viscosity of 10 mPa·s to 200 mPa·s at 25° C. when the solid content of the aqueous solution is 45%.

8. The binder according to any one of claims 1 to 7, wherein the binder has a volume average particle diameter Dv50 of 100 nm to 1000 nm.

9. A method for preparing the binder according to any one of claims 4 to 8, comprising the steps of: S11: A step of preparing the core material by polymerizing a styrene monomer and a butadiene monomer. S12: A step of polymerizing a styrene monomer, a butadiene monomer, an unsaturated acid monomer, and an unsaturated ester monomer on the surface of the core material.

10. 10. The method for preparing a binder according to claim 9, wherein in the polymerization reaction for preparing the core material, the mass ratio of the styrene monomer to the butadiene monomer is 10:(4 to 8).

11. The method for preparing a binder according to claim 9 or 10, wherein in the polymerization reaction for preparing the shell material, the mass ratio of the styrene monomer, the butadiene monomer, the unsaturated acid monomer and the unsaturated ester monomer is 10:(4-8):(1-3):(2-4).

12. A binder composition comprising the binder according to any one of claims 1 to 8 or the binder prepared by the method according to any one of claims 9 to 11, and high-viscosity sodium carboxymethylcellulose, wherein an aqueous solution of the high-viscosity sodium carboxymethylcellulose has a viscosity of 10,000 mPa·s to 20,000 mPa·s at a solids content of 1% at 25°C.

13. The binder composition according to claim 12, wherein the mass ratio of the binder to the high viscosity sodium carboxymethylcellulose is (1.1 to 3.5):

1.

14. The hydrogen atom of the hydroxy group in the high viscosity sodium carboxymethylcellulose is substituted with a substitution agent, and the substitution agent reacts with the hydroxy group to form a hemiacetal; 14. The binder composition according to claim 12 or 13, optionally, the displacing agent comprises a dialdehyde monomer, and further optionally, the dialdehyde monomer comprises one or two of glyoxal and glutaraldehyde.

15. A negative electrode slurry comprising the binder according to any one of claims 1 to 8, a binder prepared by the method according to any one of claims 9 to 11, or a binder composition according to any one of claims 12 to 14.

16. 16. The method of claim 15, wherein the negative electrode slurry includes the binder composition, comprising the steps of: S21: A step of preparing a negative electrode active material aggregate from the negative electrode active material, a portion of the high-viscosity sodium carboxymethylcellulose, a conductive agent, and a portion of a solvent. S22: Adding the remaining part of the high-viscosity sodium carboxymethylcellulose, the remaining part of the solvent, and the binder to the negative electrode active material agglomerates to prepare the negative electrode slurry.

17. The method further comprises the step of preparing the high viscosity sodium carboxymethylcellulose, the step comprising: S201: subjecting cotton fibers and an alkalizing agent to an alkalizing reaction in a mixed solution of ethanol and water; S202: After the alkalinization reaction is completed, an etherification agent is added to the reaction system to perform an etherification reaction; S203: The product of the etherification reaction is subjected to a substitution reaction with a substitution agent to prepare the high-viscosity sodium carboxymethylcellulose. Including, 17. The method for preparing an anode slurry according to claim 16, optionally, the displacement agent comprises a dialdehyde monomer, and further optionally, the dialdehyde monomer comprises one or two of glyoxal and glutaraldehyde.

18. The method for preparing a negative electrode slurry according to claim 17, wherein step S203 satisfies at least one of the following conditions I to III: I: The mass ratio of the product of the etherification reaction to the displacement agent is 100:(0.2-1.0) II: The temperature of the substitution reaction is 30° C. to 70° C. III: The time for the substitution reaction is 20 minutes to 120 minutes.

19. A negative electrode current collector, and a negative electrode active material layer located on at least one surface of the negative electrode current collector; A negative electrode sheet comprising: The negative electrode active material layer comprises the binder according to any one of claims 1 to 8, a binder prepared by the method according to any one of claims 9 to 11, or the binder composition according to any one of claims 12 to 14. A negative electrode sheet.

20. The negative electrode sheet according to claim 19, wherein the mass ratio of the binder in the negative electrode active material layer is 1.3% to 2.1%, optionally 1.5% to 2.1%, and further optionally 1.8% to 2.1%.

21. The negative electrode active material layer comprises the binder composition according to any one of claims 12 to 14, and the mass ratio of the high-viscosity sodium carboxymethylcellulose in the negative electrode active material layer is 0.6% to 1.2%, optionally 0.8% to 1.2%, and further optionally 0.9% to 1.2%. The negative electrode sheet according to claim 19 or 20.

22. A secondary battery comprising the negative electrode sheet according to any one of claims 19 to 21.

23. A battery module comprising the secondary battery according to claim 22.

24. A battery pack comprising the battery module according to claim 23.

25. An electric device comprising at least one of the secondary battery according to claim 22, the battery module according to claim 23, or the battery pack according to claim 24.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode and preparation method thereof

    CN111463401A

  • Battery electrode binder

    JP1999025989A